Detection of Correlated Protein Backbone and Side‐Chain Angle Fluctuations. (25th August 2017) - Fenwick, R. Bryn; Vögeli, Beat
Abstract: NMR methods for the characterization of local protein motions have attained a high level of sophistication. Measurement of the synchronization between those motions, however, poses a serious challenge. Such correlated motions are one of the underlying mechanisms for the propagation of local changes to remote sites and as such for information transfer. Here, we demonstrate the experimental detection of the synchronization of motion over an intermediate range. To that purpose, we designed pulse sequences for the measurement of cross‐correlated relaxation between the backbone H N −N and side‐chain H β −C β dipoles in Ile, Thr, and Val in the protein GB3. These bonds are related through two and three intervening dihedral angles. We show that the correlated motions inherent in a structural ensemble obtained from a large and diverse array of NMR probes are in excellent agreement with our measurements. Abstract : Information transfer in proteins : Correlated motions are one of the underlying mechanisms for the propagation of local changes to remote sites in proteins and as such for information transfer. We demonstrate experimental NMR detection of the synchronization of motions over an intermediate range: namely those between the backbone H N −N and side‐chain H β −C β dipoles in GB3.